A causa do contrato e sua funcionalidade - Batista, Alexandre Jamal (2021)
The cause of the contract is raised in this study as an instrument of interpretation of contractual relations. The path taken departs from the first reflections on the concept of cause, still within Aristotelian philosophy, goes through the introduction of this concept in the sphere of law − which gave rise to at least two divergent doctrinal currents − and leads to the evolution of the theory of cause, which until nowadays arouses interesting reflections. This study establishes the necessary distinctions between the various meanings of the word cause, to narrow the scope of research and deepen the investigation of the cause of the contract, from which the evolution of the theme in Law of some countries that exerted influence on our civil codification is analyzed, demonstrating how the cause of the contract was contemplated in each legal system. Having set the assumptions that the cause of the contract was deliberately removed from the 1916 civil codification and was not incorporated into the 2002 Civil Code, it is then questioned how relevant it is to our law and why we investigate this issue, considered by some too stormy. Based on the answers obtained through reasoned reflections, this paper seeks, as an unprecedented contribution, to systematize the theory of the cause of the contract in Brazilian law, placing it as an essential functional element for the interpretation of the contracts, whose integrity our law is concerned with preserving by means of the principle of objective good faith and its attached, associated and lateral duties, so that adequate contractual protection is provided in each particular case